1998
DOI: 10.1046/j.1525-1500.1998.cdoa16.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gamma-Glutamylcysteine Ethyl Ester in Cisplatin-Induced Changes in Prostanoid Concentrations in Rat Gastric and Colonic Mucosa

Abstract: We evaluated changes in gastric and colonic mucosal prostanoid contents in rats treated with cisplatin. We also determined effects of gamma-glutamylcysteine ethyl ester (GCE), a pro-drug of glutathione, on cisplatin-induced changes in prostanoid concentrations. Rats were divided into three groups--the control: 0.5 ml of physiological saline was administered intraperitoneally (i.p.); the cisplatin group: 0.5 ml of cisplatin, 10 mg/kg, was administered i.p.; the GCE + cisplatin group: GCE, 30 min before cisplati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The cysteinyl leukotriene LTC 4 , by virtue of its glutathione moiety, can bind to the same solute-carrier membrane transporter that binds glutathione-conjugated platinum, a key cellular metabolite of cisplatin and the other platinum-based chemotherapies. , This competitive interaction has been exploited in experiments using LTC 4 treatment to successfully enhance the tumor-killing potency of cisplatin in glioma cells, demonstrating that cisplatin resistance in cancer cells is at least partially mediated by active removal of the platinum−glutathione conjugate from the cell. , Essentially no work has been done studying this interaction with regard to the gastrointestinal tract, although some data have been acquired with regard to eicosanoids, cisplatin, and emesis. Indeed, one study found that pretreatment with a glutathione prodrug prior to cisplatin treatment could abolish the rise in GI prostaglandin activity associated with cisplatin and vomiting in general. It is possible the high glutathione levels caused increased production of glutathione-conjugated, nonemetogenic prostaglandin metabolites (e.g., PGJ 2 ) and shifted the metabolic balance away from production of the pro-emetic prostaglandin metabolites (PGE 2 or F 2 α).…”
Section: Eicosanoids: Synthesis Storage Release Degradation and Recep...mentioning
confidence: 99%
See 1 more Smart Citation
“…The cysteinyl leukotriene LTC 4 , by virtue of its glutathione moiety, can bind to the same solute-carrier membrane transporter that binds glutathione-conjugated platinum, a key cellular metabolite of cisplatin and the other platinum-based chemotherapies. , This competitive interaction has been exploited in experiments using LTC 4 treatment to successfully enhance the tumor-killing potency of cisplatin in glioma cells, demonstrating that cisplatin resistance in cancer cells is at least partially mediated by active removal of the platinum−glutathione conjugate from the cell. , Essentially no work has been done studying this interaction with regard to the gastrointestinal tract, although some data have been acquired with regard to eicosanoids, cisplatin, and emesis. Indeed, one study found that pretreatment with a glutathione prodrug prior to cisplatin treatment could abolish the rise in GI prostaglandin activity associated with cisplatin and vomiting in general. It is possible the high glutathione levels caused increased production of glutathione-conjugated, nonemetogenic prostaglandin metabolites (e.g., PGJ 2 ) and shifted the metabolic balance away from production of the pro-emetic prostaglandin metabolites (PGE 2 or F 2 α).…”
Section: Eicosanoids: Synthesis Storage Release Degradation and Recep...mentioning
confidence: 99%
“…389,391 Essentially no work has been done studying this interaction with regard to the gastrointestinal tract, although some data have been acquired with regard to eicosanoids, cisplatin, and emesis. Indeed, one study 392 found that pretreatment with a glutathione prodrug prior to cisplatin treatment could abolish the rise in GI prostaglandin activity associated with cisplatin and vomiting in general. It is possible the high glutathione levels caused increased production of glutathione-conjugated, nonemetogenic prostaglandin metabolites (e.g., PGJ 2 ) and shifted the metabolic balance away from production of the pro-emetic prostaglandin metabolites (PGE 2 or F 2 R).…”
Section: Gastrointestinal Tissuementioning
confidence: 99%
“…Depending on the emetogen, different neurochemical systems are involved, although several key neurotransmitters are stimulated in common. CIV is not produced via a single specific neurotransmitter, but by the release of various emetogenic signals including serotonin, substance P (SP), dopamine, and prostaglandins (Goto et al, 1998; Kasabdji et al, 1996; Saito et al, 1999; Veyrat-Follet et al, 1997). …”
Section: Introductionmentioning
confidence: 99%